1997
DOI: 10.1021/es960564w
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Biotransformation of Trichloroethylene by Hybrid Poplars

Abstract: Poplar trees were found to be capable of taking up trichloroethylene (TCE) and degrading it to several known metabolic products:  trichloroethanol, trichloroacetic acid, and dichloracetic acid. Poplars were also shown to transpire TCE in measurable amounts. To eliminate the possibility that the degradation we observed was produced solely by rhizosphere organisms, axenic poplar tumor cell cultures were tested; the cultures produced the same intermediate metabolic products. When dosed with [14C]TCE, cell culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
203
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(217 citation statements)
references
References 10 publications
9
203
1
1
Order By: Relevance
“…Plants have been shown to take up and, in some cases, to metabolize organic pollutants (6), excess nutrients (6, 7), 2,4,6-trinitrotoluene (TNT) (8,9), and metals (10,11). Work in our laboratory has demonstrated that poplar trees are able to take up and metabolize TCE both under laboratory conditions and in a field test (12)(13)(14).…”
mentioning
confidence: 89%
“…Plants have been shown to take up and, in some cases, to metabolize organic pollutants (6), excess nutrients (6, 7), 2,4,6-trinitrotoluene (TNT) (8,9), and metals (10,11). Work in our laboratory has demonstrated that poplar trees are able to take up and metabolize TCE both under laboratory conditions and in a field test (12)(13)(14).…”
mentioning
confidence: 89%
“…Poplars have been grown for relatively long periods of time with up to 50 mg/L TCE in groundwater below the trees (Newman et al, 1997) and transpirational release of TCE is observed from these trees. The amounts reported are quite small and cannot be directly related to the input levels because of technical difficulties in the transpiration measurement.…”
Section: -15mentioning
confidence: 99%
“…Organic pollutants include solvents like trichloroethylene (TCE) 2 , herbicides, atrazine 3 . Inorganic pollutants include plant macronutrients such as nitrates and phosphates, micronutrients, Cr, Cu, Fe, Mn, Mo, Ni and Zn and nonessential elements, As, Cd, Co, F, Hg, Se, Pb, V and radionuclides, 238U, 137Cs and 90Sr 4 .…”
mentioning
confidence: 99%